Synthesis of polymeric Janus superstructures via a facile synthesis method - Lim, Jerome Yi Guang (2020)
Polymeric Janus particles can be exploited for a myriad of applications. Through the understanding of interfacial tensions, theragnostic agents such as drugs or nanomaterials can be successfully encapsulated into Janus particles without losing their anisotropic structure. In this work, it is reported that how Janus superstructures, as a further extension of the Janus morphology, can be obtained by blending other synthesis parameters into the solvent emulsion process, while adhering to the requirements of the Harkin's spreading coefficient (HSC) theory. Designing such unique structures for drug delivery can provide a broader range of possibilities and applications beyond conventional Janus particles.